2021
DOI: 10.1177/0271678x211009382
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and structural brain measures in high and low sedentary older adults

Abstract: Due to its cardiovascular effects sedentary behaviour might impact cerebrovascular function in the long term, affecting cerebrovascular regulatory mechanisms and perfusion levels. Consequently this could underly potential structural brain abnormalities associated with cognitive decline. We therefore assessed the association between sedentary behaviour and brain measures of cerebrovascular perfusion and structural abnormalities in community-dwelling older adults. Using accelerometery (GENEActiv) data from The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…One of the mechanisms underlying the brain-protective effects of PA is the preservation of brain volume, or even an increase in brain volume. Observational studies have found that brain volume, particularly that of the hippocampus, is preserved in more active people ( Erickson et al, 2010 ; Flöel et al, 2010 ; Maasakkers et al, 2021 ). PA is also associated with preservation of cortical thickness ( Walhovd et al, 2014 ; Lee et al, 2016 ).…”
Section: Effects On Brain Structurementioning
confidence: 99%
“…One of the mechanisms underlying the brain-protective effects of PA is the preservation of brain volume, or even an increase in brain volume. Observational studies have found that brain volume, particularly that of the hippocampus, is preserved in more active people ( Erickson et al, 2010 ; Flöel et al, 2010 ; Maasakkers et al, 2021 ). PA is also associated with preservation of cortical thickness ( Walhovd et al, 2014 ; Lee et al, 2016 ).…”
Section: Effects On Brain Structurementioning
confidence: 99%
“…[6][7][8] Although physical activity (PA) is a protective factor for brain volume and is associated with increased brain volume in older adults, 9,10 older adults are inclined to decrease PA and increase sedentary time (ST). [11][12][13] Vulnerable older adults, including those who have physical frailty and cognitive impairment, find it difficult to engage in PA and are prone to more ST. [14][15][16][17] A recent systematic review reported a negative association between ST and brain structure: 18 ST is negatively associated with total brain volume, 19 cortical thickness, 20 and white matter volume. 21 Therefore, especially in vulnerable older adults, protective factors against brain atrophy should be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Vulnerable older adults, including those who have physical frailty and cognitive impairment, find it difficult to engage in PA and are prone to more ST 14–17 . A recent systematic review reported a negative association between ST and brain structure: 18 ST is negatively associated with total brain volume, 19 cortical thickness, 20 and white matter volume 21 . Therefore, especially in vulnerable older adults, protective factors against brain atrophy should be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Unhealthy brain aging and cognitive decline associate with a sedentary lifestyle and, at a cellular level, this is accompanied by astrocyte hypertrophy, myelin dysregulation, neurovascular dysfunction [ 1 ] and the impairment of neurogenesis [ 2 ]. Highly sedentary humans (≥8 h/day) display reduced hippocampal volumes and increased white matter (WM) hyperintensities [ 3 , 4 ] that are associated with accelerated cognitive, neuropsychiatric and functional decline [ 5 ]. In addition to the changes associated with a sedentary life, it has become clear that oral dysfunction is present in the same individuals and that this group feature is also associated with dementia or mild cognitive decline [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%